An Alternative Definition of the Notion Valuation in the Theory of Near Polygons - De Bruyn, Bart (The Electronic Journal of Combinatorics, 2009)
Valuations of dense near polygons were introduced in [9]. A valuation of a dense near polygon ${\cal S}=({\cal P},{\cal L},{\rm I})$ is a map $f$ from the point-set ${\cal P}$ of ${\cal S}$ to the set $\Bbb N$ of nonnegative integers satisfying very nice properties with respect to the set of convex subspaces of ${\cal S}$. In the present paper, we give an alternative definition of the notion valuation and prove that both definitions are equivalent. In the case of dual polar spaces and many other known dense near polygons, this alternative definition can be significantly simplified.